Combating Micronutrient Deficiency and Enhancing Food Functional Quality Through Selenium Fortification of Select Lettuce Genotypes Grown in a Closed Soilless System - Pannico, Antonio; El-Nakhel, Christophe; Kyriacou, Marios C.; Giordano, Maria; Stazi, Silvia Rita; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2019)
Selenium (Se) is an essential trace element for human nutrition and a key component of selenoproteins having fundamental biological and nutraceutical functions. We currently examined lettuce biofortification with Se in an open-gas-exchange growth chamber using closed soilless cultivation for delivering Se-rich food. Morphometric traits, minerals, phenolic acids, and carotenoids of two differently pigmented Salanova cultivars were evaluated in response to six Se concentrations (0–40 μM) delivered as sodium selenate in the nutrient solution. All treatments reduced green lettuce fresh yield slightly (9%), while a decrease in red lettuce was observed only at 32 and 40 μM Se (11 and 21% respectively). Leaf Se content increased in both cultivars, with the red accumulating 57% more Se than the green. At 16 μM Se all detected phenolic acids increased, moreover a substantial increase in anthocyanins (184%) was recorded in red Salanova. Selenium applications slightly reduced the carotenoids content of green Salanova, whereas in red Salanova treated with 32 μM Se violaxanthin + neoxanthin, lutein and β-cryptoxanthin spiked by 38.6, 27.4, and 23.1%, respectively. Lettuce constitutes an ideal target crop for selenium biofortification and closed soilless cultivation comprises an effective tool for producing Se-enriched foods of high nutraceutical value.